Revealing the mechanism of ordered two dimensional Co3S4 composite anode electro-enhanced peroxymonosulfate activation and singlet oxygen production - Chengkai Mao; Manchen Lin; Weixiong Jian; Jing Sun; Yutong Cui; Jingming Wen; Haiyang Shao; Minghong Wu (Journal of Environmental Chemical Engineering, 2026)

Predicting Rate of Penetration of Horizontal Wells Based on the Di-GRU Model - Tao Pan; Xianzhi Song; Baodong Ma; Zhaopeng Zhu; Lin Zhu; Muchen Liu; Chengkai Zhang; Tengda Long (Rock Mechanics and Rock Engineering, 2026)

Vegetation-soil-soil microbes dominate ecosystem multifunctionality in typical grasslands of the core Sanjiangyuan region on the qinghai-tibet plateau - Xin Chen; Qi Li; Dongdong Chen; Chengkai Lin; Shuyang Wen; Liang Zhao (Journal of Environmental Management, 2026)

Modulating oxidative capacity to simultaneously enhance microplastics aging and reduce adsorption performance: A novel approach to environmental remediation - Chen Lei; Lin Manchen; Mao Chengkai; Jian Weixiong; Shao Haiyang; Wu Minghong (Environmental Research, 2025)

UUV Cluster Distributed Navigation Fusion Positioning Method with Information Geometry - Lingling Zhang; Shijiao Wu; Chengkai Tang; Hechen Lin (Journal of Marine Science and Engineering, 2025)
The development and utilization of marine resources by humanity are increasing rapidly, and a single unmanned underwater vehicle (UUV) is insufficient to meet the demands of ocean exploitation. Large-scale UUV swarms present a primary solution; however, challenges such as underwater mountain ranges and signal attenuation critically impact the real-time collaborative positioning and autonomous clustering abilities of these swarms, posing major issues for their practical application. To address these challenges, this paper proposes a UUV cluster distributed navigation fusion positioning method with information geometry (UCDFP). This method transforms the navigation data of individual UUVs into an information geometric probability model, thereby reducing the impact of temporal asynchrony-induced positioning errors. By integrating factor graph theory and utilizing ranging information between UUVs, a distributed collaborative fusion positioning architecture for UUV swarms is established, enabling seamless dispersion and regrouping. In experimental evaluations, the proposed method is compared with existing techniques concerning convergence speed and the capability of UUV swarms for autonomous dispersion and regrouping. The results indicate that the method proposed in this paper achieves faster convergence and higher positioning stability during the autonomous clustering of UUV swarms, marking a notable advancement in underwater vehicular technology.

Revealing the role of interlayer spacing in radioactive-ion sieving of functionalized graphene membranes - Chengkai Mao; Haiyang Shao; Chen Huang; Lei Chen; Lin Ma; Yingfei Ren; Mengxin Tu; Hongyong Wang; Jianzhong Gu; Hongjuan Ma; Gang Xu (Journal of Hazardous Materials, 2024)

Genetically proxied PCSK9 inhibition is associated with reduced psoriatic arthritis risk - Junhong Li; Jianfeng Li; Chengkai Lin; Jiaxiang Zhou; Jianmin Wang; Fuan Wang; Haizhen Li; Zhiyu Zhou (Inflammation Research, 2024)
Background Lipid pathways play a crucial role in psoriatic arthritis development, and some lipid-lowering drugs are believed to have therapeutic benefits due to their anti-inflammatory properties. Traditional observational studies face issues with confounding factors, complicating the interpretation of causality. This study seeks to determine the genetic link between these medications and the risk of psoriatic arthritis. Methods This drug target study utilized the Mendelian randomization strategy. We harnessed high-quality data from population-level genome-wide association studies sourced from the UK Biobank and FinnGen databases. The inverse variance-weighted method, complemented by robust pleiotropy methods, was employed. We examined the causal relationships between three lipid-lowering agents and psoriatic arthritis to unveil the underlying mechanisms. Results A significant association was observed between genetically represented proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibition and a decreased risk of psoriatic arthritis (odds ratio [OR]: 0.51; 95% CI 0.14–0.88; P < 0.01). This association was further corroborated in an independent dataset (OR 0.60; 95% CI 0.25–0.94; P = 0.03). Sensitivity analyses affirmed the absence of statistical evidence for pleiotropic or genetic confounding biases. However, no substantial associations were identified for either 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors or Niemann–Pick C1-like 1 inhibitors. Conclusions This Mendelian randomization analysis underscores the pivotal role of PCSK9 in the etiology of psoriatic arthritis. Inhibition of PCSK9 is associated with reduced psoriatic arthritis risk, highlighting the potential therapeutic benefits of existing PCSK9 inhibitors.

Ultrafast strategy to self-assemble polyamidoxime PVA nanofibers with solar-induced synergy for enhancing uranium extraction from seawater - Chen Huang; Mengtao Fu; Lin Ma; Chengkai Mao; Yunyou Yao; Xiao Xu; Lu Xu; Jiaguang Han; Xiaogang Xue; Gang Xu; Minghong Wu; Haiyang Shao; et al. (Chemical Engineering Journal, 2023)

Collaborative optimization method and energy-saving, carbon-abatement potential evaluation for nearly-zero energy community supply system with different scenarios - Di Wu; Guangyao Fan; Yuxuan Duan; Ao Liu; Peiwen Zhang; Jiacheng Guo; Chengkai Lin (Sustainable Cities and Society, 2023)

Study on indoor adaptive thermal comfort evaluation method for buildings integrated with semi-transparent photovoltaic window - Haobo Wang; Chengkai Lin; Yilin Hu; Xingkui Zhang; Jun Han; Yuanda Cheng (Building and Environment, 2023)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)